S5.3d How mitochondrial complex I proteins in Candida albicans moderate phagocytosis and the production of pro-inflammatory cytokines in murine macrophages and dendritic cells. (20th September 2022) - She, Xiaodong; Zhang, Pengyi; Calderone, Richard; Liu, Weida; Li, Dongmei
Abstract: S5.3 Cellular pleomorphism and fungal virulence, September 22, 2022, 3:00 PM - 4:30 PM:   Objectives: Inhibition of respiration in Candida albicans impairs its colonization in the host tissues and causes avirulence in a murine vascular candidiasis model. Accordingly, blockage of the mitochondrial electron transport chain (ETC) of C. albicans by respiratory inhibitors promotes phagocytosis by increasing exposure of glucan which could be due to the mannan reduction. In our model, we have reported that 85% mannan reduction in goa1Δ, a deletion mutant of an ETC Complex I (CI) regulator, oppositely decreased phagocytosis. To understand such a difference, we broaden our investigation with three CI respiratory subunit mutants, which are either fungal-specific (nuo1Δ and nuo2Δ) or broadly conserved subunits (ndh51Δ) for cell wall analysis and innate immune responses. Methods: We characterized mutant cell wall defects in these mutants, then analyzed their respective survival in macrophages. Fungal internalization into macrophages was visualized under fluorescent microscopy and live-cell imaging and analyzed through flow cytometry analysis. Cytokine production in dendritic cells (DCs) infected by fungal cells was measured by xMAP technology and the transcriptional profiles of murine macrophages-infected by different mutants were compared. Results: We find that phosphopeptidomannan (PPM) reduction in goa1Δ and nuo1Δ and phospholipomannan (PLM) reduction in nuo2Δ correlate with massive inhibition of cytokine. PPM loss in nuo1Δ or goa1Δ fails to promote phagocytosis but promotes opsonized neutrophil killing. The cause of PPM insufficiency results from reduced phosphorylation of the Cek1 MAPK in goa1Δ and nuo1Δ. In contrast other three mutants, phagocytosis and cytokine production of ndh51Δ more resemble WT cells, which have shown an ∼ 30% glucan reduction due to a defective Mek1 MAPK response. The divergent immune responses to these CI mutants are shown at the transcriptional level in infected macrophages. We noted that those well-characterized host receptors such as dectins and TLR2/4 for PPM, PLM, and glucan ligands are not significantly affected at 1 h post-infection. However, the scavenger receptor CD36, integrin ICAM, and growth factor receptors are downregulated along with a generally downregulated endocytosis and antigen processing/presentation. In addition, the host metabolic processes, oxidative stress-induced senescence, apoptosis, and signaling pathways such as Ras1/Erk5, the cAMP/CREB, and TLR9 pathway, are each individually affected in the host cells. Conclusion: We speculate that mitochondrial signals of fungal origin may also be sensed by the host immune cells to coordinate the immune responses together with cell replication and metabolism during the early stage of infection.